Cyber-War - Richards, J. author. aut Link
VIII, 99 p.
Keywords: Cyber-War provides a critical assessment of current debates around the likelihood and impact of cyber warfare. Approaching the subject from a socio-political angle, it argues that destructive cyber war has not yet been seen, but could be a feature of future conflict.